Jornalismo local: espaço para o debate do desenvolvimento regional - Borba, Raíza Goi (2019)
This study aims to analyze the periodical Jornal da Manhã, from the municipality of Ijuí in Rio Grande do Sul, as a space for the dissemination of news related to regional development and, consequently, a channel capable of promoting debates and discussions about themes of interest in the Northwest region of State. The research was performed using the qualitative method, using the content analysis procedure for the interpretation of the data. For its accomplishment, 100 editions of the aforementioned periodical were analyzed, contemplating the evaluation of 3,684 reports or news in the period from July 2017 to June 2018. From the comparative analysis between the evaluated news and the demands presented by the Strategic Plan of Regional Development 2015 -2013, prepared by the Regional Development Council (Corede) - Northwest Colonial Region, it was possible to verify that regional development is present in the local journalism agenda, but not in an expressive way, broadening the studies of the relationship between journalism and development.